A Scoping Review of Citizen Science Approaches in Chronic Disease Prevention - Marks, Leah; Laird, Yvonne; Trevena, Helen; Smith, Ben J.; Rowbotham, Samantha (Frontiers in Public Health, 2022)
Background: Citizen science approaches, which involve members of the public as active collaborators in scientific research, are increasingly being recognised for their potential benefits in chronic disease prevention. However, understanding the potential applicability, feasibility and impacts of these approaches is necessary if they are to be more widely used. This study aimed to synthesise research that has applied and evaluated citizen science approaches in chronic disease prevention and identify key questions, gaps, and opportunities to inform future work in this field. Methods: We searched six databases (Scopus, Medline, Embase, PsycInfo, PubMed and CINAHL) in January 2022 to identify articles on the use of citizen science in prevention. We extracted and synthesised data on key characteristics of citizen science projects, including topics, aims and level of involvement of citizen scientists, as well as methods and findings of evaluations of these projects. Results: Eighty-one articles reported on citizen science across a variety of health issues, predominantly physical activity and/or nutrition. Projects primarily aimed to identify problems from the perspective of community members; generate and prioritise solutions; develop, test or evaluate interventions; or build community capacity. Most projects were small-scale, and few were co-produced with policy or practice stakeholders. While around half of projects included an evaluation component, overall, there was a lack of robust, in-depth evaluations of the processes and impacts of citizen science projects. Conclusions: Citizen science approaches are increasingly being used in chronic disease prevention to identify and prioritise community-focused solutions, mobilise support and advocacy, and empower communities to take action to support their health and wellbeing. However, to realise the potential of this approach more attention needs to be paid to demonstrating the feasibility of using citizen science approaches at scale, and to rigorous evaluation of impacts from using these approaches for the diverse stakeholders involved.